Sintering processes in direct ink write additive manufacturing: A mesoscopic modeling approach. (1st May 2019) - Abdeljawad, Fadi; Bolintineanu, Dan S.; Cook, Adam; Brown-Shaklee, Harlan; DiAntonio, Christopher; Kammler, Daniel; Roach, Allen
Abstract: Direct ink write (DIW) is an emerging additive manufacturing technique that allows for the fabrication of arbitrary complex geometries required in many technologies. DIW of metallic or ceramic materials involves a sintering step, which greatly influences many of the microstructural features of the printed object. Herein, we explore solid-state sintering in DIW through a mesoscopic modeling framework that is capable of capturing bulk and interface thermodynamics and accounting for various mass transport mechanisms. Simulation results of idealized geometries identify regimes in materials parameter space, where densification rates are enhanced. With the aid of several statistical and topological descriptors, the role of particle size distribution (PSD) on the microstructural evolution is explored and quantified. More specifically, it is found that a bi-dispersed PSD enhances pore shrinkage kinetics. However, bi-dispersity yields microstructures with pores that are highly eccentric, an effect that could be detrimental to the mechanical properties of the printed material. On the whole, our modeling approach provides a capability to explore the phase space of DIW process parameters and determine ones that lead to optimal microstructures. Graphical abstract: Image 1